Learning Media Based E-Learning Management at SMK Negeri 1 Purbalingga - PujiPunarwo, Yosep Win (2012)
The objectives of the research are (1) to describe characteristics of learning media making based e-learning at SMK Negeri 1 Purbalingga; (2) to describe characteristics of learning media material based e-learning at SMK Negeri 1 Purbalingga; (3) to describe characteristics of learning media usage based e-learning usage at SMK Negeri 1 Purbalingga. It is descrptive qualitative research and ethnography design which describes learning media based-learning Management The data are in the forms of information consisting of systematic thought, sentences, and experience based on specific context. The data sources are event, document, informant, and artifact. Techniques used in data collection are in depth interview, documentation and observation. Data analysis of this research is Qualitative data analysis , the analysis of data arranged in a site for description. The research results show that: (1) making of learning media based e-learning is started by coordination meeting conducted by the principal, vice principal of curriculum, and vice principal of infrastructure to discuss about preparing e-learning concept that will be used. The Principal appoint officers (admin) who are technically mastered the field of IT to prepare programs to be held. In making learning media based based on e-learning, the school prepares the facilities needed. In making the media along with training or briefing to teachers in order to make them able to adapt to the e-learning media and mastering it to be used as a learning media for student. Teachers make teaching preparations appropriate with e-learning concept then upload it to e-learning site owned by school; (2) The materials of learning media based e-learning are in the form of learning materials or module or assignments and communications using computer and internet. The materials are uploaded through the school's site, blog, and LCD media. The material provided in the form of soft file in word or power point and completed with picture, graphs, or charts.The materials of learning media based e-learning at SMK Negeri 1 Purbalingga are in the form of website and do not open source; (3)The use of learning media based e-learning via internet, the material can be accessed anywhere and anytime by students through the school's website.To download the material, teachers give code or key of the material. The material uploaded can only be downloaded by the school's citizens or students who know the key. The guests only can access profile menu or activities held by the school. The usage of learning media based e-learning is also done with LCD.The obstacle faced in using learning media based on e-learning is the teachers' ability which is not evenly related to IT.